Psychological Resilience As A Factor In The Prevention Of Depression Among Adolescents And Youth In The Digital Environment - Regina Rinatovna Pulatova (Peerian Journals Publishing, 2025)
This article addresses the need to develop and implement a multifactor model for the early prevention of depressive disorders in adolescents and young adults. Given the polyetiological nature of depression in youth, the study focuses on the integration of psychoemotional, social, and neurobiological risk factors. Directions for screening and early intervention are presented, including the assessment of emotional regulation, family environment, digital stress, and neuropsychological traits. The effectiveness of an interdisciplinary approach in building resilience against depression is substantiated.
Keywords: Depression; youth; prevention